ANALISIS SARANA DAN PRASARANA SMA MUJAHIDIN PONTIANAK: ANALISIS SARANA DAN PRASARANA SMA MUJAHIDIN PONTIANAK - Maulana, Bagus; Andoni, Sulistyo Sapta; Rabihati, Etty; Riyanti, Rika (RETENSI, 2021)
Senior High School (abbreviated SMA) is a secondary level of formal education in Indonesia after graduating from Junior High School (or its equivalent). High school is taken within 3 years, starting from grade 10 to grade 12. The school that will be studied by the author has several problems that occur, therefore the author is interested in conducting research on facilities and infrastructure in the school. Therefore, the author submitted a questionnaire in order to find out what problems occurred in the school. The purpose of this study is that students are able to analyze the facilities and infrastructure of the Pontianak Mujahidin High School, able to overcome the problems that occur in the environment. The methods used in solving this problem are qualitative methods and quantitative methods. The qualitative method is subjective in nature, the research interacts directly with the object being studied. Meanwhile, quantitative methods are objective, independent research is what is being studied. Facilities and infrastructure problems that occur include the parking area which is enlarged by 33% from the initial area and the elevation of the parking area. The second is the widening of the dimensions of the enlarged drainage channel in order to prevent flooding. Finally, by increasing the dimensions of the classroom lighting so that the classroom lighting is sufficient.